(untitled) (Journal of history, 2021)
In the historiography of Kazakhstan, the scientific problem of the spread of Islam and its role in the history of the Kazakhs occupies an important place. As is known throughout the Soviet period from the 1920s to 1991, due to the domination of atheism and anti-Islamic syndrome, scholars did not have the opportunity to comprehensively study the Islamic factor in the history and culture of the Kazakh people. Suffice it to say that the name of Khoja Ahmed Yasawi was banned, Sufism was interpreted as a reactionary phenomenon of mysticism (this word had a negative meaning in Soviet science). In addition, in academic works, Islam was interpreted as the faith of the social elite, while the masses allegedly always professed Shamanism. In general, the problem of the Islamization of the Turks and the role of Islam for the Kazakh nation remained a taboo and ideologically engaged issue. The historiographic review over the years of Independence identifies key problems, contradictions and limitations of Sovietological concepts, in particular, about “syncretism” and “superficial Islam”, and shows the ways of research in the conditions of Independence and intensification of international cooperation. Attention is drawn to the concept of regional Islam and the recognition of self-identification of an ethnic group as its main criterion for determining its religious affiliation, to modern trends and achievements of researchers aimed at studying both theoretical and factual aspects of the problem of Islamization. A general description of the most important studies, their novelty, at the same time, the presence of pluralism of scientific opinions, prospects for studying the role and place of Islam in the history of the Turks and the history of Kazakhstan in general is given. The essence of the author’s concept on the history of the Islamization of the territory of Kazakhstan in the Middle Ages is also reflected. Key words: anti-Islamic syndrome, syncretism, regional Islam, religious identity, civilizational approach, international relations, spiritual factor, fundamental research.